MENGGELEDAH EKSISTENSI KAUM MARHAEN DALAM MENGISIH DAN MEMAKNAI KEBIJAKSANAAN SISTEM POLITIK DI INDONESIA: Tinjauan Berfilsafat Politik - F.X. Armada Riyanto - Yosef Usman; Fransiskus Xaverius Eko Armada Riyanto; Pius Pandor (Sanjiwani: Jurnal Filsafat, 2025)
This paper is about the existence of the small, the simple or the marginalized in contemporary politics. "Philosophizing Politics" means searching or exploring the values of political wisdom that is not only the elite, rich, or high educational background but also the small people also have a place to play politics properly. This paper aims to analyze how the existence of small, simple or marginalized people succeeds in the political system in Indonesia. The existence of the marhaen in Indonesia seems to be considered starting to retreat, which has an impact on the arrogance of the marhaen of the elite, rich or high education background, and there is a tendency to negate others as secondary subjects. The attitude of arrogance and the tendency to negate others is a habit or even a culture of authority applied by some or a group of people to cultivate an arrogant and apathetic attitude towards mutually agreed rules which then negate others as secondary subjects such as seeing the most dominant group, derivative, tribe, or culture. The method used in this paper is qualitative research by means of a literature study sourced from the book Political Philosophy coupled with other sources such as books and scientific articles from journals that support this paper.The result found in this paper is that the existence of the marhaen or the small, simple or marginalized people in Indonesia is considered not to have a strong basis of authority from its basis, a culture of arrogance, apathy towards rules, and a tendency to negate others as the second subject is considered weak in politics. This is due to its human resources who are less aware of the true and precise meaning of "political wisdom y", thus making the existence of the marhaen experience a setback. The lack of understanding of the meaning of politics, the existence of the marhaen. in the case of negating the marhaen in contemporary politics in Indonesia is the main reason why "the small, the simple or the marginalized in Indonesia are considered not to have a strong basis of authority from their basis in politics" get attention and a decent and balanced place in politics.